Don't let the square root symbol intimidate you. It's just a symbol. Just rewrite the original equation as a quadratic in sqrt(x). Multiply through by 2 and rearrange to get x + 2*sqrt(x) - 24 = 0. Now use the quadratic formula. a=1, b=2, c=-24 gives us sqrt(x) = {-6,4}. Reject sqrt(x)=-6 because that is nonsense. Thus the only answer is x = 4^2 = 16.
Root x= minus 6
It isn't obvious to me why both of the solutions can't be positive.
Don't let the square root symbol intimidate you. It's just a symbol. Just rewrite the original equation as a quadratic in sqrt(x). Multiply through by 2 and rearrange to get x + 2*sqrt(x) - 24 = 0. Now use the quadratic formula. a=1, b=2, c=-24 gives us sqrt(x) = {-6,4}. Reject sqrt(x)=-6 because that is nonsense. Thus the only answer is x = 4^2 = 16.
Great explanation! 👍
Minus 6